Analysis of Spatial and Temporal Evolution of Water Resources Carrying Capacity in Jilin Province Based on Improved TOPSISI Model - HOU Yue; LI Zhijun; WANG Huafan; HUANG Jiajun (Renmin Zhujiang)
The carrying capacity state of water resources is an important reference for stable social and economic development.On the basis of the water resources bulletins,statistical yearbooks,and national economic and social development bulletins of Jilin Province from 2004 to 2019,18 indicators such as the development and utilization rate of water resources are selected,and four evaluation subsystems including one for water resources are constructed.Moreover,the TOPSIS model based on the game theory and the combination weighting method is used to analyze the spatial and temporal evolution of water resources carrying capacity (WRCC) and the coupling coordination in the nine administrative divisions of Jilin Province.The results indicate that except for Changchun City,Baicheng City,and Siping City,where the multi-year WRCC is in Class Ⅲ,i.e.,on the verge of overload,the other six cities and prefecture are all in Class Ⅱ with a good carrying capacity.The comprehensive evaluation value of each city or prefecture from high to low satisfies the following order:Tonghua City,Yanbian Korean Autonomous Prefecture,Jilin City,Songyuan City,Baishan City,Liaoyuan City,Siping City,Baicheng City,and Changchun City.In general,the WRCC in Jilin Province is in a good condition.With the improvement in the local development and utilization rate of water resources,the coupling coordination of WRCC subsystems is gradually improved,and the stress resistance is further enhanced.